Is there any difference between the in situ and systemic IL-10 and IFN-ã production when clinical forms of cutaneous sporotrichosis are compared? - Morgado, Fernanda N. (2016)
Fungus of the Sporothrix schenckii complex can produce skin lesions in humans, commonly lymphocutaneous (LC) and fixed (F) forms of sporotrichosis. Some authors have suggested that clinical forms are influenced by differences in virulence and genetic profile of isolates. But little is known about the role of immune response in determining the clinical outcome of sporotrichosis. To verify the profile of systemic and in situ IFN-ã and IL-10 expression in sporotrichosis patients, and consequently to detect any difference between the two compartments and/or clinical presentation, we quantified the number of IFN-ã and IL-10 producer peripheral blood mononuclear cells stimulated with S. schenckii antigen (Ss-Ag) by Elispot, and quantified cytokines expression by in situ immunohistochemistry in the same patient. Three groups were formed: 1- LC (n = 9); 2- F (n = 10); 3- healthy individuals (n = 14). All sporotrichosis patients produced high amounts of systemic IFN- ã when compared to uninfected individuals. No differences were observed between LC and F groups. Regarding in situ IL-10 expression, a difference between LC and F groups was observed: LC lesions presented higher amounts of IL-10 than F lesions differently from systemic IL-10 which showed similarities. Our data suggests that LC lesions present higher IL-10 expression which could be related to regulatory mechanisms for compensating the tissue injury, however favoring fungal persistence in the lesions. Surprisingly, there were no differences in systemic and in situ IFN- ã expression between CL and F patients, although it was significantly higher expressed in these patients than in healthy individuals.